Immunology and Genetic of Preeclampsia - Norma C. Serrano (Clinical and Developmental Immunology, 2006)
Preeclampsia is a disease characterized by hypertension and proteinuria in the third trimester of pregnancy. Preeclampsia is a major cause of maternal mortality, and fetal death, especially in developing countries, but its aetiology remains unclear. Key findings support a causal role of superficial placentation driven by immune mal maladaptation, which then lead to reduced concentrations of angiogenic growth factors and to an increase in placental debris in the maternal circulation resulting in a maternal inflammatory response. Epidemiological research has consistently demonstrated a substantial familial predisposition to preeclampsia. Unfortunately, the conquest of the genes explaining such a individual susceptibility has been proved to be a hard task. However, genetics will also inform us about causality of environmental factors, and then serve as a tool to prioritize therapeutic targets for preventive strategies.